Optimization of the use of sorghum flour, peanuts, and moringa leaves in the making of high-protein gluten-free biscuits [Optimasi penggunaan tepung sorgum, kacang tanah dan daun kelor pada pembuatan biskuit non-gluten tinggi protein] - Wulandari, Endah; Indiarto, Rossi; Arifin, Heni Radiani; Talitha, Shabrina Gitta (Jurnal Teknologi & Industri Hasil Pertanian, 2024)
Protein is one of the macronutrients that the body needs in large quantities in addition to carbohydrates and fats. Eating high-protein biscuits can be one way to meet daily protein needs. Biscuits made from sorghum flour, peanuts, and Moringa leaves can produce non-gluten biscuits high in protein. This study aimed to determine the optimal balance of using sorghum flour, peanuts, and moringa leaves to produce high-protein biscuits with acceptable sensory values. The research method used is an experimental method with descriptive data analysis. The optimization method uses the Response Surface Methodology (RSM) experimental design with a central composite design (CCD). The best biscuit formula, as a result of the RSM experimental design optimization, has a protein nutrient content of 8.71%, 2.60% moisture content, 2.60% ash content, 32.99% fat content, and 53.85% carbohydrate content. The combination of using flour significantly affects the texture of the biscuits but does not significantly affect the color. Using composite flour consisting of 60% sorghum flour, 37% peanuts, and 4% moringa leaves to manufacture non-gluten biscuits can produce biscuits that are high in protein and have physicochemical properties and good sensory acceptability.